2003
DOI: 10.1002/adma.200305241
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐Induced Orientation of a Film of Ladderlike Polysiloxane Bearing Dual Photoreactive Side Groups

Abstract: The control of the orientation of liquid crystalline molecules is essential in liquid crystal displays (LCDs), and is usually achieved by coating an alignment film on the conductive ITO (indium tin oxide) glass surface. The photo-alignment (PA) technique as one promising alternative to the widely used conventional rubbing process of a polyimide (PI) substrate has been studied extensively in the last decade, because it provides a simple and non-contact fabrication process suitable for advanced thin film transis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…According to our previous description of the photoalignment mechanism, [15] it is suggested that the influence of exposure conditions is related to the rate of two photoreactions. Only when UV light with proper intensity and dose is applied, are the photo-induced isomerization and crosslinking triggered simultaneously and the reorientation both in and out of plane results.…”
Section: Influence Of Irradiation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous description of the photoalignment mechanism, [15] it is suggested that the influence of exposure conditions is related to the rate of two photoreactions. Only when UV light with proper intensity and dose is applied, are the photo-induced isomerization and crosslinking triggered simultaneously and the reorientation both in and out of plane results.…”
Section: Influence Of Irradiation Conditionsmentioning
confidence: 99%
“…[3a,4a,6,7,9±11] On the other hand, the polymers containing photocrosslinkable cinnamate or coumarin groups have been regarded as preferred candidates for PA films since Schadt and co-workers demonstrated their good performance in inducing stable, uniform alignment. [2±4,12±14] As recently stated in our previous report, [15] a novel ladder-like polysiloxane containing dual photoreactive groups, cinnamoyl and p-nitroazobenzene, attached in a side-on fashion, was designed and synthesized for generating high-quality photoalignment layers with controllable pretilt angle. The mechanism of photo-induced alignment and generation of pretilt angle was elucidated by some integrated spectroscopic methods as follows: the photo-induced isomerization and cycloaddition reactions take place cooperatively and give rise to consistent contributions to the homogeneous alignment; the direction-selective E±Z±E isomerization cycle of gradually enriched azobenzene groups leads mainly to an out-of-plane (spatial) reorientation and a reasonably large tilt angle.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, moderate annealing before and after illumination can markedly improve the alignment uniformity by self-healing of defects. [12] 4. Pseudo-SPS-Based SHG/NLO Polymer Materials SHG/NLO organic polymers have attracted much attention owing to their high NLO activity and good processability.…”
Section: à2mentioning
confidence: 99%
“…It is noteworthy that ladder-like polymers have greater resistance to irradiation as well as thermal and chemical degradation in comparison to their single-stranded counterparts. 16,17 Besides, ladder-type arrays should have planar and rigid π-π structures that facilitate electron delocalization and enhance conjugation. 17 A series of ladder polymers with various linkers, including the ferrocene moiety, the azobenzene group, multilayer planar oligoaryl chromophores, hexaperi-hexabenzocoronenes, cubane, cuneane, and cyclooctatetraene have been synthesized by the ROMP of bis(norbornene) derivatives.…”
Section: Introductionmentioning
confidence: 99%